(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Earthquakes may create various kinds of causalities like loss of life and damage of property depending upon its magnitude; causalities could range from small property damage to landslides and a long range of liquefaction. Secondary effects like fire; blockage on services such as water supply, electricity, and transportation; and communication disruption are even more disastrous.Man-made infrastructures are however the major contributor of casualties during earthquake devastations. These structures therefore should be carefully designed and constructed.It is very important to develop new technologies to minimize these losses. Thus, we started to do research regarding these new techniques and to improve our knowledge and become aware of these recent methods and their usage in our daily life to optimize earthquake effects on our structures. We cannot make fully earthquake-proof structures but we will reduce its damage and make structures earthquake resistant. In this research paper, we will discuss modern technologies that make our structure earthquake resistant.